2018
DOI: 10.1007/s11626-018-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of calcification by osteoblasts cultured on hydroxyapatite surfaces with adsorbed inorganic polyphosphate

Abstract: Inorganic polyphosphate has been expected to accelerate bone regeneration. However, there are limited evidences to prove that polyphosphate adsorbed on the surface of a hydroxyapatite plate enhances calcification of cultured osteoblasts. In this study, we examined the effect of polyphosphate adsorbed onto the surface of a hydroxyapatite plate on the attachment, proliferation, differentiation, and calcification of osteoblasts. After hydroxyapatite plates were soaked in solutions of polyphosphate, the plate surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The PolyP promotes osteocalcification and bone mineralization in both mouse and human osteoblastic cells [7][8][9][10]. Regarding the effect of polyP on cell calcification, Kawazoe et al [9] reported that it promotes cell calcification in murine osteoblastic MC3T3-E1 cells, while Morita et al [11] reported that inorganic polyphosphate-adsorbed hydroxyapatite enhances bone regeneration, and cellular calcification of MC3T3-E1 cells is enhanced on the surface of polyP-adsorbed hydroxyapatite [12]. Kawazoe also reported that in the calcification of MC3T3-E1 cells, polyP is utilized as a phosphate source and that this is accompanied by an increase in polyphosphatase activity [9].…”
mentioning
confidence: 99%
“…The PolyP promotes osteocalcification and bone mineralization in both mouse and human osteoblastic cells [7][8][9][10]. Regarding the effect of polyP on cell calcification, Kawazoe et al [9] reported that it promotes cell calcification in murine osteoblastic MC3T3-E1 cells, while Morita et al [11] reported that inorganic polyphosphate-adsorbed hydroxyapatite enhances bone regeneration, and cellular calcification of MC3T3-E1 cells is enhanced on the surface of polyP-adsorbed hydroxyapatite [12]. Kawazoe also reported that in the calcification of MC3T3-E1 cells, polyP is utilized as a phosphate source and that this is accompanied by an increase in polyphosphatase activity [9].…”
mentioning
confidence: 99%
“…133 In addition to its role as a substrate, polyP has also been shown to have a direct influence on biomineralisation pathways by inducing the expression of bone formation markers OPN, OC and ALP, leading to the mineralisation of pre-osteoblast MC3T3 cells. 105,134 Increased ALP expression has also been shown in SaOS-2 cells, and an increase in intracellular calcium was seen when calcium-polyP was used as a substrate, but not with Ca, Pi, or polyP alone. 135 As well as a role in bone formation, polyP has been shown to increase cartilage production, but for a short time before it is degraded by the polyphosphatases released by chondrocytes.…”
Section: The Curious Role Of Polyphosphatesmentioning
confidence: 99%
“…Compared with HA, the polyP/HA hybrid particles, which had bioactivity similar to that of Ca-polyP nanoparticles, could enhance the metabolic activity of SaOS-2 cells and human MSCs and upregulate the gene expression of COL-1 and ALP, providing a better design and improved selection for bone tissue engineering materials. PolyP adsorbed on the surface of an HA plate can also enhance the calcification of the cultured osteoblasts [90]. Wang et al [91] confirmed that the mixing of amorphous calcium carbonate particles with amorphous Ca-polyP particles can enhance the proliferation rate of human MSCs in in vitro studies.…”
Section: Application Of Polyp Materialsmentioning
confidence: 99%